PENGARUH SASARAN YANG JELAS DAN TERUKUR, DESENTRALISASI, INDIKATOR PENGUKURAN KINERJA DAN INSENTIF TERHADAP KINERJA ORGANISASI SEKTOR PUBLIK (Studi Empiris atas Pemerintah Daerah di Wilayah Provinsi D I Yogyakarta) - , Anita Primastiwi, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to give empirical evidence about the impact of clear and measurable goals, decentralization, performance measurement indicators, and incentives on performance of local governmental units in the of D. I. Yogyakarta Province. This research refers to Verbeetenâs research (2008) about the impact of performance-based management to performance of public sector organizations in the Netherlands. The population is local government units of D. I. Yogyakarta. The samples are SKPDâs chairmen or chairwomen, those are the chairmen or chairwomen of governmental services in province level (D. I. Yogyakarta) and regencial level (Kota Yogyakarta, Kabupaten Sleman, Kabupaten Gunung Kidul, Kabupaten Bantul, and Kabupaten Kulon Progo). They must be in his or her position for at least one year. This research analyzes their perception about statements in the questionaire. The data was analized by partial least square (PLS) with SmartPLS Version 2.0 Like the result of Verbeetenâs research (2008), this research found an empirical evidences that clear and measurable goals has positive impact on both quantity performance and quality performance. But, inconsistent with Verbeetenâs research (2008), this research gave an empirical evidence that incentives has negative impact on the quantity performance and positive impact on quality performance.